Cognitive-Pragmatic Description of the Content of Artistic Discourse (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Artistic discourse occupies a special place in human communication, conveying complex emotions, ideas and aesthetic experiences. This article offers a cognitive-pragmatic account of the content of artistic discourse, exploring the interaction of cognitive processes and pragmatic aspects in the formation and transmission of meaning.